Transport properties and concrete quality : (Wiley, 2007)
This title is based on the workshop on Transport Properties & Concrete Quality, held at the campus of Arizona State University on October 10-12, 2005. During this meeting, scientific aspects of the relevant relationships between materials, mechanisms, processes, and service life were discussed. Provides a useful resource for understanding the most valuable aspects of cement-based materials, with topics ranging from the current state of practice, to theory, simulation, and testing and specifications. Logically organized and carefully selected articles give insight into the need to better integrate aspects of materials science, mechanics, modeling, and testing in developing tools of understanding the durability in cement-based materials